Analysis Of Generation Z's Intercultural Communication Patterns Via Tiktok/Instagram: An Islamic Perspective - Rismayanti Rismayanti; Muhammad Irham; Ahmad Tamrin Sikumbang; Yushilda Usman; Ahmad Syukri Siregar; Fitri Agraini Siregar; Safii Simbolon (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study examines the communication competencies and strategies of intercultural Generation Z on TikTok and Instagram through a qualitative netnography approach. Research results show the existence of dialectics between a logic-algorithmic platform that curates exposure culture and Gen Z users who form an algorithmic imaginary. By dramaturgical, Gen Z differentiates presentation self: TikTok is working as a room-experimentation culture, with low (low-stakes), with spontaneity structured as spontaneity. On the other hand, Instagram becomes an arena for high-stakes demands curation of global-local aesthetics, even though Gen Z is getting around it with secondary accounts (finsta) for more free expression. Interaction is coloured by the hybridization of linguistics and semiotics, including practices such as translanguaging and Indoglish, as well as the meanings of migration emojis. In the Islamic perspective, this cross-cultural phenomenon reflects draft lita'arafu (mutual knowledge). However, the implementation of digital demand tabayyun and Islamic digital literacy-based muraqabah as an internal filter against the negative impact of social media.